IMPLEMENTATION OF MANAGEMENT FUNCTIONS IN THE CONGREGATIONAL DAWN PRAYER MOVEMENT PROGRAM BY THE INDONESIAN MOSQUE COUNCIL OF BINJAI CITY - Al Anshori, M.Fauzan; Soiman (Department of Research and Community Service at the Ummul Quro Al-Islami Bogor Institute, 2025)
The Congregational Fajr Prayer Movement program implemented by the Indonesian Mosque Council of Binjai City is a religious initiative that aims to revive the spirit of the community in performing the Fajr worship in congregation This research is carried out to find out how the management functions are applied to the Congregational Fajr Prayer Movement program by the Indonesian Mosque Council of Binjai City. This research uses qualitative methods and case study approaches. The data sources in this study consist of two data sources, namely primary data sources and secondary data sources. Primary data sources are carried out by interviews and observations of related parties in the Congregational Fajr Prayer Movement program and secondary data sources used from relevant documents. The results of the study show that the Congregational Dawn Prayer Movement Program implements management functions, such as planning, organizing, mobilizing, as well as supervision and evaluation. Even so, there are several problems, such as weak coordination in planning, mismatch of tasks and expertise in organization, the absence of a reward system that lowers motivation in mobilization, and lack of clarity at the supervision stage. The success of the program is highly dependent on strengthening coordination, adjusting tasks to competencies, implementing clear performance indicators, and developing a structured evaluation and sanction system. With this solution, it is hoped that the program will be more effective and the participation of pilgrims can increase sustainably